Molecular hydrogen positively influences lateral root formation by regulating hydrogen peroxide signaling. (December 2022) - Liu, Feijie; Wang, Yueqiao; Zhang, Guhua; Li, Longna; Shen, Wenbiao
Abstract: Although a previous study discovered that exogenous molecular hydrogen (H2 ) supplied with hydrogen-rich water (HRW) can mediate lateral root (LR) development, whether or how endogenous H2 influences LR formation is still elusive. In this report, mimicking the induction responses in tomato seedlings achieved by HRW or exogenous hydrogen peroxide (H2 O2 ; a positive control), transgenic Arabidopsis that overexpressed the hydrogenase1 gene ( CrHYD1 ) from Chlamydomonas reinhardtii not only stimulated endogenous hydrogen peroxide (H2 O2 ) production, but also markedly promoted LR formation. Above H2 and H2 O2 responses were abolished by the removal of endogenous H2 O2 . Moreover, the changes in transcriptional patterns of representative cell cycle genes and auxin signaling-related genes during LR development in both tomato and transgenic Arabidopsis thaliana matched with above phenotypes. The alternations in the levels of GUS transcripts driven by the CYCB1 promoter and expression of PIN1 protein further indicated that H2 O2 synthesis was tightly linked to LR formation achieved by endogenous H2, and cell cycle regulation and auxin-dependent pathway might be their targets. There results might provide a reference for molecular mechanism underlying the regulation of root morphogenesis by H2 . Highlights: Both exogenous and endogenous H2 can induce plant lateral root development. H2 O2 acts downstream of H2 signaling in lateral root branching. H2 O2 acts on the early stages of lateral root primordium formation elicited by H2 .